Vascular Remodeling in Pulmonary Arterial Hypertension: The Potential Involvement of Innate and Adaptive Immunity - Tobal, Rachid; Potjewijd, Judith; Empel, Vanessa P. M. van; Ysermans, Renee; Schurgers, Leon J.; Reutelingsperger, Chris P.; Damoiseaux, Jan G. M. C.; Paassen, Pieter van (Frontiers in Medicine, 2021)
Pulmonary arterial hypertension (PAH) is a severe disease with high morbidity and mortality. Current therapies are mainly focused on vasodilative agents to improve prognosis. However, recent literature has shown the important interaction between immune cells and stromal vascular cells in the pathogenic modifications of the pulmonary vasculature. The immunological pathogenesis of PAH is known as a complex interplay between immune cells and vascular stromal cells, via direct contacts and/or their production of extra-cellular/diffusible factors such as cytokines, chemokines, and growth factors. . These include, the B-cell - mast-cell axis, endothelium mediated fibroblast activation and subsequent M2 macrophage polarization, anti-endothelial cell antibodies and the versatile role of IL-6 on vascular cells. This review aims to outline the major pathophysiological changes in vascular cells caused by immunological mechanisms, leading to vascular remodeling, increased pulmonary vascular resistance and eventually PAH. Considering the underlying immunological mechanisms, these mechanisms may be key to halt progression of disease.